Where is Alcatraz? - Medina, Nico 1982-; Groff, David 1956- (New York, New York Grosset & Dunlap, an imprint of Penguin Random House, 2016)
"Escape from the ordinary and break into Alcatraz, America's most famous prison! The island of Alcatraz has always been a place that's fascinated visitors, from the Native American tribes who believed it was home to evil spirits to the Spanish explorers who discovered the island. In modern times, it was a federal prison for only 29 years, but now draws over a million visitors each year. Learn the history of America's most famous prison, from its initial construction as a fort in the 1800s, to its most famous residents such as Al Capone and 'Machine Gun' Kelly. Where Is Alcatraz? also chronicles some of the most exciting escape attempts--even one that involved chipping through stone with spoons and constructing rafts out of raincoats!"--
Different countries
Includes bibliographical references (page 108)
1
Keywords: United States Penitentiary, Alcatraz Island, California -- History -- Juvenile literature; JUVENILE NONFICTION / History / Symbols, Monuments, National Parks, etc; JUVENILE NONFICTION / History / United States / 20th Century; JUVENILE NONFICTION / History / United States / State & Local; Prisons -- California -- Alcatraz Island -- History -- Juvenile literature; Alcatraz Island (Calif.) -- History -- Juvenile literature